The Effect of Azolla Flour (Azolla microphylla) in Commercial Ration on the Performance of 75 Days Old KUB Chicken - Juli Mutiara Sihombing; Mangonar Lumbantoruan; Partogi Hutapea; Ade Putra Tadeus Siringo-ringo (Talenta Publisher, 2025)
Research on KUB chickens (Ayam Kampung Unggul Balitbangtan) needs to be conducted to support the progress of livestock farming in the field of poultry livestock production. This study determines the effect of giving Azolla flour in commercial rations on the performance of 75-day-old KUB chickens. The study was conducted at the Animal Biology Laboratory, Faculty of Animal Husbandry, HKBP Nommensen University, Medan in Simalingkar A Village. Pancur Batu District, Deli Serdang Regency. This study was conducted for 75 days. On days 1-7 days, commercial feed was given. At the age of 8-75 days, commercial feed was given and Azolla flour (Azolla microphilla) was added. The design used in the study was a Completely Randomized Design with four treatments and five replications, the research treatment was the comparison of azolla flour with commercial rations given for KUB chicken feed, namely Azolla flour levels of 0%, 2%, 4% and 6%. The research data were analyzed by analysis of variance. The results of the analysis showed that the provision of azolla flour with different treatments did not have a significant effect on ration consumption but had a very significant effect on body weight gain and feed conversion of 75-day-old KUB Chickens with the best treatment, namely P1 (Azolla 2%) with a Daily Body Weight Gain value of 15.81 grams/head/day and a conversion value of 3.01. In conclusion is that application of Azolla flour could improve KUB body weight gain and conversion.